Col d'Olen, soil temperature 2007-2019 - Freppaz, Michele; Viglietti, Davide (Zenodo, 2020)
Dataset provides information about soil temperature, soil C and N dynamics at different sites in the alpine tundra, along an elevational gradient from 2500 to 2900 m asl during the period 2005-2018. The soil temperature is measured continuously from 2007 to 2019 while the soil and the water samples are collected during the snow free season. The ongoing studies aimed at investigating how the meteorological variables affect the biogeochemistry of seasonally snow covered areas, with a special focus on the effect of the snow cover duration on soil and water C and N dynamics during the growing season.